PERTUMBUHAN BIBIT PULAI DARAT (Alstonia angustiloba Miq.) PROVENAN PENDOPO, MUARA ENIM, SUMATERA SELATAN PADA APLIKASI KOMPOSISI MEDIA TUMBUH DAN DOSIS PUPUK NPK YANG BERBEDA - Mashudi Mashudi (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
The aim of this experiment was to investigate effect of media growth composition and NPK fertilizer dosage toward growth ability of A. angustoiloba from Pendopo Provenance, Muara Enim, South Sumatera. Completely Randomized Design of factorial with two factors (growth media composition and fertilizer dosage) and four levels of each factors were used. Four replications were used with five seedlings per replication. The effects of those treatments were evaluated through seedling height growth, stem diameter growth and number of leaves. The result showed that media composition variations gave very significant effect on height growth and number of leaves of A. angustiloba seedling for 4 months. The best height growth was produced of top soil + compost (1:1) media (48,51 cm) and the best number of leaves was produced of top soil media (19,89). The fertilizer dosage variations gave very significant effect on height growth, stem diameter and number of leaves of A. angustiloba seedling for 4 months. The best height growth (49,58 cm), stem diameter (5,93 mm) and number of leaves (20,24) were produced by 1 g NPK fertilizer dosage. Interaction of media composition and fertilizer dosage gave significant influence on height growth and stem diameter of A. angustiloba seedling for 4 months.The best height growth (52,7 cm) was produced by interaction of top soil + compost (1:1) media and 1 g dosage of NPK fertilizer and the best stem diameter (6,5 mm) was produced by interaction top soil and 0.5 g dosage of NPK fertilizer.